Metabolomic Differentials in Women With and Without Fibromyalgia. Issue 1 (5th September 2019) - Menzies, Victoria; Starkweather, Angela; Yao, Yingwei; Thacker, Leroy R.; Garrett, Timothy J.; Swift‐Scanlan, Theresa; Kelly, Debra Lynch; Patel, Param; Lyon, Debra E.
Abstract : A nontargeted plasma metabolomic analysis was conducted to compare differentially expressed metabolites in women with and without fibromyalgia (FM) using data and samples collected from two parent studies in women with FM ( n = 20) and comparative data collected from newly recruited age‐matched women ( n = 20). Blood plasma samples were analyzed for metabolite content using liquid chromatography mass spectrometry. Consolidation of positive and negative ion mode metabolomics data with fold change (>2 or <0.5) and variable importance of projection scores ≥1 revealed statistically significant metabolites comparing samples from women with and without FM. Metabolite profiles in patients with FM differed from the comparison group in energy, lipid and amino acid metabolites reflecting heightened oxidative stress, inflammation, and tryptophan degradation in patients with FM. Study results may contribute to further identification of unique metabolomic profiles enhancing understanding of the pathophysiology of FM and for the development of effective therapeutic options.